Kaizen: a Japanese philosophy and system for business excellence. Issue 5 (21st September 2015) - Macpherson, Wayne G.; Lockhart, James C; Kavan, Heather; Iaquinto, Anthony L.
Abstract : Purpose: – The purpose of this paper is to develop a definitive and insightful working definition of kaizen for practitioners and academics in the West through which they may better understand the kaizen phenomenon and its intangible but critical underpinning philosophy. Design/methodology/approach: – A phenomenological study of the utility of kaizen within in the bounds of active kaizen environments in name Japanese industrial organisations was conducted over a three-year period in Japan. The research explored how Japanese workers acknowledge, exercise, identify and diffuse kaizen in a sustainable manner. Findings: – Kaizen is found to be a broad philosophical approach to work that serves different purposes for different members of the organisation, where no universal definition appears to exist yet differing ideologies are tolerated. Kaizen in Japan has a considerably deep meaning: it channels worker creativity and expressions of individuality into bounded environments, and creates an energy that drives a shared state of mind among employees to achieve proactive changes and innovation in the workplace. Originality/value: – This paper competently bridges the Japanese-Anglosphere cultural divide in social and business contexts. It contributes to the development of practitioner understanding of the utility of kaizen in Japan through unhindered cross-cultural research methodology, enabled by researcher competency and fluency in Japanese language and culture.